Adubação mineral e espécies nativas na revegetação de base de poço de petróleo em área de restinga - Rosa, Rayane (2020)
The Atlantic Forest is one of the richest biomes in biodiversity, but the growing urbanization and extractive activities have caused the degradation of these areas and a consequent imbalance of the entire natural cycle of the environment, which makes t